Sweet potato extract alleviates high-fat-diet-induced obesity in C57BL/6J mice, but not by inhibiting pancreatic lipases - Liu, Tiange; Wu, Fan; Chen, Kejing; Pan, Bingna; Yin, Xifeng; You, Yilin; Song, Zhixuan; Li, Dan; Huang, Dejian (Frontiers in Nutrition, 2022)
Sweet potato is widely consumed as a healthy and nutritive vegetable containing bioactive constituents for health promotion. This study investigated the beneficial impact of white-fleshed sweet potato extract (SPE) on high fat diet (HFD)-induced obese mice. First, SPE, in which resin glycoside was found as the dominant constituent, was suggested as a potential anti-obesity agent, because 20–70% pancreatic lipase inhibition was measured with SPE by in vitro turbidity assay and pNPP assay. Hence, next, the effect of SPE on obese mice was detected by oral administration of HFD supplemented with 6% SPE on C57BL/6J mice for 9 weeks. Surprisingly, being the opposite of what was typically observed from a lipase inhibitor such as orlistat, the fecal fat content in SPE-fed obese mice was decreased (p < 0.01). Meanwhile, 6% SPE supplement indeed significantly ameliorated HFD-induced obesity in mice, including body weight gain, fat accumulation, adipocyte enlargement, insulin resistance and hepatic steatosis (p < 0.05). The improved liver steatosis was found associated with a down-regulating action of SPE on nuclear factor kappa B activation in HFD-fed mice. The anti-obesity influence of SPE was also confirmed on the HepG2 cell model for non-alcoholic fatty liver disease. These results indicate that SPE, as a dietary supplement, has the great potential for weight control and treating hepatic steatosis, possibly through a different action mechanism from that of orlistat.